Synthesis, Spectroscopic, Thermogravimetric and Electrochemical Characterization of Triphenylphosphineoxide Complexes of the type [MClx (Ph3PO)6-x] (M = Cu(II), Co(II), x = 2; M = Fe(III), x = 3) - Das, Pankaj; Baruah, Jayantajit; Tamuly, Pranjal (Asian Journal of Chemistry, 2010)
Triphenylphosphineoxide (PPh3O) complexes of the type [MClx(Ph3PO)6-x] (1, M = Cu(II), x = 2; 2, M = Co(II), x = 2; 3, M = Fe (III), x = 3) were synthesized. The complex 1 and 2 were synthesized by the solid state melt down reaction between MCl2.nH2O (M = Cu, n = 2; M = Co, n = 6) and four molar equivalent of PPh3O ligand whereas the complex 3 was synthesized by refluxing anhydrous FeCl3 with four molar equivalents of PPh3O in acetonitile. The complexes were characterized by melting point determination, elemental analysis, conductivity measurement, FAB-Mass, FTIR, UV-Vis, DTA-TGA, cyclic voltammetry (complex 1 and 2) and ESR analysis. The molecular stoichiometry of the complexes was established on the basis of elemental analysis and the TGA weight loss patterns and the molecular mass were determined by FABmass spectra. The complex 1 and 2 show a molecular ion peak at m/z 1245 and at 1241, respectively corresponding to [M-1]+ peak, whereas the complex 3 shows a peak at m/z 961 due to [M-Cl]+. The molecular geometries of the complexes were proposed on the basis of UV-Vis and ESR analysis. The cyclic voltammetric study of the Cu(II) complex, 1, shows a quasi-reversible redox peak for the Cu(II)/Cu(III) couple whereas the Co(II) complex 2 shows an irreversible peak due to oxidation of Co(II) to Co(III).